2004
DOI: 10.1039/b313637j
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected chromogenic properties of 1,3,3-trimethylspiro(indoline-2,3′-[3H]naphtho [2,1-b][1,4]oxazine) in the solid phase: photochromism, piezochromism and acidichromism

Abstract: New chromogenic properties of a spirooxazine {1,3,3-trimethylspiro(indoline-2,3 0 -[3H]naphtho[2,1-b][1,4]-oxazine), SO} are presented in this work. This molecule was found to be photochromic and piezochromic in the pure microcrystalline solid phase and also exhibited acidichromism when kept in contact with a hydrogen-donating solid phase. Photochromism was observed under continuous UV irradiation. Biexponential thermal bleaching followed the interruption of irradiation. Piezochromism was detected by applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…To investigate the light induced isomerization processes and to determine the type of photochromism, UV/vis absorbance spectra before and after irradiation with UV light (λ=365 nm, 30 min) of all compounds 1 to 4 were recorded under inert conditions. Switching of pure SP−O is only possible, when deposited as thin films, in single‐crystalline phase at very low temperatures or by irradiation with intense UV light (high pressure Hg lamp) . Here, photoswitching of SP−O embedded into the different MOF frameworks was achieved by a common UV lamp at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the light induced isomerization processes and to determine the type of photochromism, UV/vis absorbance spectra before and after irradiation with UV light (λ=365 nm, 30 min) of all compounds 1 to 4 were recorded under inert conditions. Switching of pure SP−O is only possible, when deposited as thin films, in single‐crystalline phase at very low temperatures or by irradiation with intense UV light (high pressure Hg lamp) . Here, photoswitching of SP−O embedded into the different MOF frameworks was achieved by a common UV lamp at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This finding showed that the pressure induced the cleavage of the C-O bond in pryan ring and resulted in the piezochromic reaction of solid CzNP accompanied by the change of the color. Meanwhile the absorption band was broadened and obviously red-shifted compared with that in solution caused by the compact aggregation of the ring-open isomers, due to the compression of sample [45,46].…”
Section: Piezochromic Propertiesmentioning
confidence: 96%
“…be soluble in its immediate environment to give a true solution rather than a dispersion as most commercial classes do not exhibit useful photochromism as solids [21,22].…”
Section: Properties Of Commercial T‐type Photochromic Dyesmentioning
confidence: 99%